The Application of Combined Phytoremediation Greywater Treatment in A Single House - Ni Nyoman Nepi Marleni; Ristie Ermawati; Nurul Alvia Istiqomah (Journal of the Civil Engineering Forum, 2021)
A report showed 22% of households in Indonesia did not have a proper sanitation facility in 2018 and this caused the potential discharge of their wastewater directly to the surface water, thereby, polluting the water and its surrounding environment. The quality of water resources is also declining nationwide due to pollution and this affects the cost of water treatment, therefore, it is necessary to determine the most effective treatment method to reduce this pollution. However, one of the breakthroughs observed to have met the criteria of low cost, simple operation and maintenance, and energy-saving is greywater treatment using plants (phytotechnology) combined with solar ultraviolet (UV) system. This research was, therefore, conducted to evaluate the performance of the coupled greywater treatment and investigate the possibility of its implementation in the actual condition of a selected single house. Moreover, the physical treatment and phytoremediation were combined with solar disinfection treatment, and the units selected include a collection and sedimentation chamber, filter, phytoremediation, and solar disinfection chamber. The flowrate was measured based on the difference in water level over time while the influent and effluent quality was evaluated at the inlet of the sedimentation chamber and outlet of the disinfection chamber. The results showed the organic efficiency removal was up to 92% while the solids content was found to be high at 49% and the system was able to effectively remove the ammonia at 57% and reduce the pathogenic bacteria by 88%. Moreover, the treated water quality known as the effluent met all the requirements of the Provincial Regulation of Central Java No. 5 of 2012 and Class 3 standard (water for cultivation of plants and fisheries) of Indonesian Government Regulation No. 82 of 2001. However, it did not meet the standard for toilet flushing water according to the standard from U.K, U.S.A, and Australia. This means the treatment system was unable to produce an effluent with the ability to replace the water use indoor. Therefore, it is recommended that an advanced treatment system for greywater such as Submerged Membrane Bioreactor be applied to maximize the intake of treated greywater for indoor and outdoor uses.